PENERAPAN METODE PEMBELAJARAN ACTIVE LEARNING DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS VIII.B DI SMP KARTIKA XX-2 MAKASSAR: PENERAPAN METODE PEMBELAJARAN ACTIVE LEARNING DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Aulia Ramadani; Abdul Wahab; Ratika Nengsi; Andi Bunyamin; Muhammad Syahrul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study discusses "The Application of Active Learning Methods in Improving Student Learning Outcomes in Islamic Religious Education Subjects Class VIII.B at SMP Kartika XX-2 Makassar. This research is motivated by the low learning outcomes of students who are still far from the Minimum Completeness Criteria (KKM). This study aims to describe the application of the Active Learning method in improving student learning outcomes in Islamic Religious Education subjects. The research method used is Class Action Research (PTK) with reference to the Kemmis and Mc Taggart models which consist of two cycles. Each cycle includes stages of planning, action, observation, and reflection. The subjects in this study are students of class VIII.B SMP Kartika XX-2 Makassar with a total of 29 students. Data collection techniques use observation, interviews, tests and documentation. The analysis data used are quantitative data analysis data and qualitative data. The results of the study show that the application of the Active Learning learning method has succeeded in significantly improving student learning outcomes. The average student score increased from 61.38 (27.59% completeness) in the pre-cycle to 72.76 (51.72% completeness) in the first cycle and then reached 86.90 (89.66% completeness) in the second cycle. Quantitatively, there was an increase in completeness of 24.13% and an average score of 11.38 from pre-cycle to cycle I, as well as an increase in completeness of 37.94% and an average score of 14.14 from cycle I to cycle II. The data proves that student learning outcomes have increased and have met the classroom success indicator, which is 75 with the application of the Active Learning learning method.